IMPLEMENTASI APLIKASI BERBASIS DESKTOP PADA APOTEK AFIFA MENGGUNAKAN METODE WATERFALL - Kalsum, Ummy; S. P, Basuki Rakhim.; Mawazi, Mawazi (LPPM Universitas Bina Bangsa, 2023)
Building an information system requires a good and clear understanding of the system that will be used in terms of system procedures, input, output and things that affect system performance both in the short and long term. Public Health Clinics, data processing systems for handling medicine supplies still use the common method, namely manual data collection and ordering of medicines. Paradigm. 2018. Afifa Pharmacy is a general pharmacy where data processing is still done manually, this causes frequent errors or human errors, especially in recording sales data and drug supply data. This research aims to implement a desktop-based application using the waterfall method. The results of this research are that recording sales data and drug supply data using an application is more effective, efficient and accurate